The Interrelationship of Global Information Technologies, Artificial Intelligence, And Virtual Reality (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the interrelationship between Artificial Intelligence (AI) and Virtual Reality (VR), two pivotal technologies driving significant advancements across various sectors globally. It examines how the integration of AI and VR enhances user experiences, offering innovative solutions in fields such as healthcare, education, entertainment, and training. The article highlights how AI algorithms can personalize and adapt VR environments in real-time, creating immersive and interactive experiences that were once unimaginable. Furthermore, it discusses the potential benefits and challenges of these technologies, emphasizing their transformative impact on industries and society. The ongoing evolution of AI and VR promises to revolutionize the way we interact with digital environments, with far-reaching implications for the future of human-computer interaction.